Intermittent hypoxic preconditioning reduces the risk of peri- and postoperative complications during on-pump cardiac surgery - I. Dhif; O. S. Glazachev; Af. A. Bestavashvili; Ch. Sinlyan; E. P. GulyaevaSeltsovskaya; N. O. Kuznetsova; E. A. Syrkina; V. V. Smirnova; E. N. Dudnik; P. Sh. Chomakhidze; B. M. Tlisov; R. N. Komarov; et al. (Российский кардиологический журнал)
Aim. To assess the effect of intermittent hypoxic-hyperoxic exposures (IHHE) on the outcomes of on-pump cardiac surgery.Material and methods. This prospective, single-center, randomized, controlled study was conducted in 110 patients with heart valve defects and/or aortic pathology from the cardiac surgery clinic of the I. M. Sechenov First Moscow State Medical University. The total sample was randomly divided into a group of patients who underwent IHHE (n=66) and a control group of patients who underwent placebo procedures with ambient air (n=44). The frequency and structure of intra-and postoperative complications were analyzed within 30 days after surgery. The presence of cognitive impairment, as well as serum troponin I and lactate concentrations were analyzed before and after surgery.Results. Peri- and early postoperative complications such as cardiac death, non-fatal infarction and acute heart failure occurred significantly less frequently in patients treated with IHHE compared with placebo group (1,6% vs 16,7%, p=0,009; 1,6% vs 16,7%, p=0,009; 6,3% vs 33,3%, p<0,001, respectively). The median troponin I values 24 hours after surgery were 1,068 ng/ml (0,388-1,397 ng/ml) in the IHHE group and were significantly lower compared to the control group (1,980 ng/ml (1,068-3,239 ng/ml)). The serum lactate level after surgery was 1,8±0,7 mmol/l in the IHHE group and was significantly lower compared to the control group — 2,4±1,2 (p=0,05). Cognitive function, assessed by MOCA and MMSE tests, turned out to be significantly higher in patients who underwent a preoperative IHHE. No significant complications or serious adverse events were observed during the IHHE procedures.Conclusion. The use of individually adapted hypoxic preconditioning procedures reduces the incidence of peri- and postoperative complications, which is accompanied by a lower ischemia-reperfusion myocardial injury during artificial circulation with preservation of cognitive functions. IHHE procedures ramp up prehabilitation of patients referred for on-pump surgery of heart defects and aortic pathology.